Acceptance and Perception of Nigerian Patients to Medical Photography. Issue 3 (18th June 2012) - Adeyemo, W.L.; Mofikoya, B.O.; Akadiri, O.A.; James, O.; Fashina, A.A.
ABSTRACT The aim of the study was to determine the acceptance and perception of Nigerian patients to medical photography. A self‐administered questionnaire was distributed among Nigerian patients attending oral and maxillofacial surgery and plastic surgery clinics of 3 tertiary health institutions. Information requested included patients' opinion about consent process, capturing equipment, distribution and accessibility of medical photographs. The use of non‐identifiable medical photographs was more acceptable than identifiable to respondents for all purposes (P = 0.003). Most respondents were favourably disposed to photographs being taken for inclusion in the case note, but opposed to identifiable photographs being used for other purposes most especially in medical websites and medical journals. Female respondents preferred non‐identifiable medical photographs to identifiable ones (P = 0.001). Most respondents (78%) indicated that their consent be sought for each of the outline needs for medical photography. Half of the respondents indicated that identifiable photographs may have a negative effect on their persons; and the most commonly mentioned effects were social stigmatization, bad publicity and emotional/psychological effects. Most of the respondents preferred the use of hospital‐owned camera to personal camera/personal camera‐phone for their medical photographs. Most respondents (67.8%) indicated that they would like to be informed about the use of their photographs on every occasion, and 74% indicated that they would like to be informed of the specific journal in which their medical photographs are to be published. In conclusion, non‐identifiable rather than identifiable medical photography is acceptable to most patients in the studied Nigerian environment. The use of personal camera/personal camera‐phone should be discouraged as its acceptance by respondents is very low. Judicious use of medical photography is therefore advocated to avoid breach of principle of privacy and confidentiality in medical practice.